Production and characterization of a novel asymmetric 3D printed construct aimed for skin tissue regeneration - Miguel, Sónia (2019)
Skin is a complex organ that act as the first protective barrier against any external threat. After an injury occurs, its structure and functions must be re-established as soon as possible. Among different available skin substitutes (epidermal, dermal and dermo-epidermal), none of them is fully capable of reproducing/re-establishing all the features and functions of native skin. Herein, a three-dimensional skin asymmetric construct (3D_SAC) was produced using electrospinning and 3D bioprinting techniques. A poly(caprolactone) and silk sericin blend was electrospun to produce a top layer aimed to mimic the epidermis features, i.e. to provide a protective barrier against dehydration and hazard agents. In turn, the dermis like layer was formed by printing layer-by-layer a chitosan/sodium alginate hydrogel. The results obtained in the in vitro assays revealed that the 3D_SAC display a morphology, porosity, mechanical properties, wettability, antimicrobial activity and a cytotoxic profile that grants their application as a skin substitute during the healing process.